Ethos as manifested in the supervisors' use of the four leadership styles - Magana, Lin-Lyn F.
This study dealt with the efour leadership styles as a manifestations of the supervisors' ethos. It sought to describe how ethos plays a significant role on leadership. The dimensions of ethos were adopted and modified from the study conducted by Madrigal (1992): a. Moral qualifications - with integrity, trustworthy, dependable, and a good example to subordinates, b. Intelligence - as being intelligent, knowledgeable of the equipment's functions, being listened to by the subordinates and industrious, c. Expertise - as being expert in the field, experienced, trained, reliable, broadminded and has a good track record. At the same time, the four leadership styles were adopted from the "One Minute Manager" authored by K. Blanchard et al. (1985): a. Directing, b. Coaching, c. Supprting, d. Delegating.